Periodic optical filter based on high-Q nested multiple coupled-knots resonator. (1st June 2022) - Yi, Yating; Zhao, Haiyan; Jiang, Yuxuan; Brambilla, Gilberto; Fan, Ya-Xian; Wang, Pengfei
Abstract: A periodic optical filter based on nested knots resonator structure is proposed. The structure consists of a knot resonator with a number of smaller coupled-knot-resonators nested in it, similarly to a dual-bus coupled ring resonator, where the end bus terminations are connected to form a Mach–Zehnder interferometer. The variation of periodical transmission output is shown to be mainly due to the change of field components that results in constructive or destructive interference between the nested multiple coupled-knots and the outer loop. The coupling matrix formalism is used to investigate the influence of the number of coupled-knots and their coupling coefficient on the transmission spectrum. The theoretical result shows that the temperature effect can be eliminated by immersing the resonator in ethanol solution. The output spectrum from a fabricated sample with high-Q is also presented. The device is capable of generating a periodical spectral filtering response and has potential applications as a filter or interleaver.